ISOLASI BAKTERI SELULOLITIK DARI PERAIRAN DUMAI - Waidil Anuar; Andi Dahliaty; Christine Jose (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Dumai water samples are estimated to contain cellulolytic microorganisms because of farm waste. Samples 930 from Sei Pakning and 931 from Rupat Strait were water samples containing cellulolytic bacteria taken from Dumai. In this study the production of cellulase enzymes from cellulolytic bacteria in samples of 930 and 931 used CMC as a substrate. Cellulase is an enzyme that catalyses the hidrolisis of β-1-4-glycosidic bond of cellulose. All of the isolates produced cellulase and were able to degrade cellulose. The results indicated that 1% substrate gave the highest activity of Cellulase in the 931-4A (Rupat strait) (1.186 ± 0.319) x 10 -3 U/mL, whereas the highest specific enzyme activity of the bacterial isolates was 930-1C (8.438 ± 0.109) x 10 -3 U/mg.